The aspects of legal regulation on staffing of procuratorial authorities of the Russian Federation and the Republic of Kazakhstan - Mukanbetkaliyev, Arman; Amandykova, Saule; Zhambayev, Yerzhan; Duskaziyeva, Zhanar; Alimbetova, Alida (Opción, 2018)
This article considers the issues of improving the legal regulation of the staffing of procuratorial authorities of the Russian Federation and the Republic of Kazakhstan into account the views of leading Russian lawyers, scientists and materials practical activities of state bodies. This article discusses some aspects of the admission and service in bodies and organizations of Prosecutor’s office, such as requirements for individuals appointed to positions of prosecutors of the limitations, prohibitions and responsibilities connected with work in bodies and institutions of Prosecutor’s office, powers of appointment and dismissal procedure for certification of public prosecutors.